Preseason clinical shoulder test results and shoulder injury rate in adolescent handball: A prospective study on female and male elite players - Asker, M.; Waldén, M.; Källberg, H.; Holm, L. W.; Skillgate, E. (Journal of Orthopaedic & Sports Physical Therapy, 2020)
Study Design: Prospective cohort study. Background: Shoulder injuries are common in handball. Shoulder weakness, scapular dyskinesia and range of motion (ROM) deficits are associated with shoulder injury in adults, but studies of adolescent players are scarce. Objective: To investigate if elite adolescent female and male handball players with shoulder muscle weakness, deficits in shoulder rotation ROM or joint position sense (JPS), or scapular dyskinesia in preseason have an increased shoulder injury rate compared to players not having these characteristics. Methods: 341 uninjured players (452 player-seasons, 50% females) had isometric external rotational (IER), internal rotational (IIR), abduction (IABD) and eccentric external rotational (EER) shoulder strength, shoulder ROM, JPS, and scapular dyskinesia measured during pre-season. Players were monitored weekly regarding match- and training hours and shoulder injuries during one or two seasons. We used multivariable Cox proportional hazard models to calculate hazard rate ratios (HRR) related to the first injury with 95% confidence intervals (95% CI). Results: 48 new shoulder injuries were reported during the two seasons. In females, the HRR for IER was 2.37 (95% CI 1.03-5.44), for IIR 2.44 (95% CI 1.06-5.61), and for scapular dyskinesia 1.53 (95% CI 0.36-6.52). In males, the HRR for IER was 1.02 (95% CI 0.44-2.36), for IIR 0.74 (95% CI 0.31-1.75), and for scapular dyskinesia 3.43 (95% CI 1.49-7.92). There were no associations between new shoulder injuries and deficits in ROM or JPS. Conclusion: In adolescent elite handball, male players with pre-season scapula dyskinesia, and female players with pre-season internal or external rotation shoulder weakness, had an increased shoulder injury rate.